Structural phase transition and manifestation of eddy currents in IR reflection spectra of PbSnTe semiconductor films. (March 2020) - Yakovlev, V.A.; Muratov, A.V.; Kucherenko, I.V.; Vinogradov, V.S.; Novikova, N.N.; Karczewski, G.; Schreyeck, S.
Abstract: Infrared reflection spectra of thin (∼60 nm) Pb1− x Sn x Te ( x = 0.25, 0.53, 0.59) films grown by molecular beam epitaxy on GaAs/CdTe hybrid substrates have been measured at frequencies from 20 to 5500 cm −1 and temperatures from 5 to 300 K. The spectra have been used to determine temperature-dependent transverse phonon and plasmon frequencies in the films, which has made it possible to identify a structural phase transition at T C ≈ 50 K. The plasma frequency of the films has been shown to increase with decreasing band gap on cooling from 300 to 77 K. The increase in plasma frequency is mainly attributable to the increase in carrier concentration and a transition of the carriers from vortex states on the film surface to the valence band.